Applying welfare science to cetacean strandings : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Zoology at Massey University, Albany, New Zealand - Boys, Rebecca M (Massey University, 2022)
Animal welfare science can provide critical knowledge to inform ethical wildlife management and human intervention efforts. Despite live stranding events being recognised by the International Whaling Commission as a major welfare concern for free-ranging cetaceans, little research has to date, been conducted on stranded cetacean welfare. Live cetacean stranding events offer a quintessential exemplar of wildlife management, where assessment or integration of welfare has been limited in the decision-making process. This thesis contributes new understanding of how welfare science can be applied to cetacean stranding events to inform decision-making processes. Here, the first welfare-centric data regarding live stranded cetaceans is presented. Specifically, this research presents novel contributions to science via: (1) conceptualisation of stranded cetacean welfare and survival likelihood; (2) recognition of key knowledge gaps and concerns that must be addressed to ensure optimal welfare and survival likelihood outcomes; (3) identification of potential valuable and practical indicators for assessing stranded cetacean welfare and survival likelihood; (4) evidenced feasibility of welfare indicator application to live cetacean stranding events; (5) incorporation of indicators to undertake holistic welfare assessments; (6) identification of potential welfare implications of strandings management, including efficacy of euthanasia; and (7) provision of key recommendations and requirements to ensure humane end-of-life outcomes for non-viable stranded cetaceans. This thesis documents inextricable links between animal welfare and survival likelihood of stranded cetaceans and demonstrates a clear need for integration of welfare science alongside conservation biology at live stranding events. Systematic, standardised data collection and welfare-centric assessment of stranded cetaceans can, if applied scientifically, inform intervention decisions, to ensure consistent guidance and improve strandings management to safeguard humane outcomes for affected cetaceans. Collectively, this research provides a significant contribution to the current scientific understanding of stranded cetacean welfare, by providing key knowledge required for the development of a welfare assessment framework that can support decision-making at stranding events.
Keywords: Cetacea; Stranding; Effect of stress on; Condition scoring; Decision making; Moral and ethical aspects; Animal welfare; Case studies; Euthanasia of animals; 300306 Animal welfare